How not to write a thesis or dissertation : a guide to success through failure - Sundström, Mikael (Edward Elgar Publishing, 2020)
"If you thought a book about thesis writing would make for wearisome reading, think again! In seven entertaining and enlightening chapters, Mikael Sundström sheds light on the trials and tribulations of academic writing, offering guidance on how to become a doyen of academic disaster - and, more importantly, how to avoid that fate. Prepare to consider your academic writing in a whole new way. Guiding readers through the many stages of thesis writing, this dynamic book provides a comprehensive and rigorous methodology that encompasses the crucial aspects of the dreaded dissertation. It follows the writing process, from drafting the research question and composing the first line, to constructing an impressive argument and finishing a thesis with finesse. Featuring concrete tips on academic penmanship and regular 'How Not to Fail' boxes, Sundström identifies the potential pitfalls that lead to dissertation disaster - and expertly lays out a path to success. This useful guide will be crucial reading for postgraduate students preparing to write theses and dissertations, as well as undergraduate students undertaking longer academic papers for the first time. It will also be a convenient reference guide for course leaders in need of a bank of ideas to assist their students"--